543. Perceived Ease of Use and Operator Performance of a rapid Multiplex PCR Diagnostic System in a Near Patient Setting. (15th December 2022) - Ky, Ashley; Bastar, Jeffrey; Holmberg, Kristen; Bay, Hana; Jones, Tiffani; Hearst, Bethany; Davis, Thomas; Selvarangan, Rangaraj; Banerjee, Dithi; Hueschen, Leslie A; Cohen, Daniel M; Enne, Virve; et al.
Abstract: Background: Access to multiplex molecular diagnostic tests for the rapid and accurate diagnosis of pharyngitis and other respiratory infections is limited in the near patient setting, but has potential to improve patient outcomes and antibiotic stewardship. The BioFire ® Respiratory/Sore Throat (R/ST) Panel (bioMérieux, Salt Lake City, UT), designed for use with the BioFire ® SpotFire System, is an Investigational Use Only (IUO) PCR-based sample-to-answer diagnostic test that identifies four bacteria and 10 viruses from nasopharyngeal swabs or throat swabs in ∼16 minutes. This study evaluated the ease of use and operator performance of the IUO R/ST Panel in the near patient setting. Methods: A total of 35 test operators representative of the intended users in the near patient setting (i.e. non-laboratory professionals) participated across five study sites in the US and UK. Only Instrument and Panel Quick Guide training materials were provided during the eight months of R/ST Panel testing. Upon study completion, anonymous questionnaires were administered to assess operators' perceived ease of use of the BioFire SpotFire System, R/ST Panel testing, and training materials; the accuracy of results interpretations were also evaluated. Further, results obtained by operators in the near patient setting and trained laboratory personnel were evaluated for reproducibility. Results: Overall, 96.9% of operators reported that the system and panel were easy to use and that the provided training materials were sufficient to allow the user to perform the testing. The success rate of obtaining valid results on the initial test was 96.9%, similar to the rates observed for trained laboratory personnel. Reproducibility between site operators and trained laboratory personnel demonstrated an overall positive percent agreement of 99.0%. Conclusion: The BioFire SpotFire System is an easy to use system that can be installed and operated in a near patient setting with minimal training. The R/ST Panel is also easy to use with minimal risk for user error. Implementation of this new system may aid in timely diagnosis and appropriate management of pharyngitis and other respiratory infections. Data presented are from assays that have not been cleared or approved for diagnostic use. Disclosures: Ashley Ky, MLS(ASCP), bioMérieux: Employee|bioMérieux: Stocks/Bonds Jeffrey Bastar, PhD, bioMerieux: Employee|bioMerieux: Stocks/Bonds Kristen Holmberg, n/a, bioMerieux: Employee Hana Bay, BS, Biomerieux: Employee|Biomerieux: Stocks/Bonds Tiffani Jones, PhD, bioMerieux: Employee|bioMerieux: Stocks/Bonds Rangaraj Selvarangan, BVSc, PhD, D(ABMM), FIDSA, F(AAM), BioFire: Grant/Research Support|Luminex: Grant/Research Support Virve Enne, BSc PhD, Biomerieux: Advisor/Consultant Cynthia Andjelic, PhD, bioMerieux: Employee.